Tussen revolusionisme en pasifisme: Die ontplooiing van Reformatoriese verset in die sestiende eeuse Protestantisme (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2024)
The developments in sixteenth century Protestant resistance theory served as an influential catalyst in the transition from medieval to modern constitutionalist ideas. The first decades of the Protestant Reformation witnessed two important perspectives unfolding in support of the notion of the supremacy of law and resistance to tyranny: The idea of the office of rulers detached from ecclesiastical structures in the fold of Luther and his followers, and the Calvinist notion of governmental power controlled by the people or their representatives. By the time of the Magdeburg Admonition (1550), the fusion of the Lutheran and Calvinist ideas of institutional restraints on monarchical power had established a platform for justifying active resistance to tyranny in the public sphere. It also confirmed the principle based on natural law theory that individuals have the right (and duty) to protect life, limb, property and honour in matters of private law. The fusion of the Lutheran and Calvinist political ideas as facilitated by the increasing emphasis on the idea of the common weal was the most important regulative principle and focal point of the duties of monarchs and rulers. Johann Eisermann’s work on the common weal provided Protestant political thought with a clearer view of the borderline between just political governance and tyranny. Francois Hotman’s Franco Gallia (1573) postulated the mixed constitution in which authority is shared between the king and the community as a standard against which subsequent political and legal changes must be evaluated. Hotman’s discourse on the ancient regime in France highlights the principle that the king is nothing more than a magistrate and is constantly subject to removal by the people for violating the duties of his office. Furthermore, the ancient public council’s power of creating and deposing kings, the control of legislation and supervision of the ordinary conduct of government. Theodor Beza pursued the avenue of the Admonition of the Lutheran town of Magdeburg against the Interim of the German Emperor, Charles V, in 1548: A king who persecutes the true religion is no longer a legitimate authority since he was originally established to defend the Law of God. Regional princes, the magistrates of towns, and other inferior magistrates may resist him because they too have been established to do the will of God. Hubert Languet’s Vindiciae contra tyrannos (1574-1575) is not only a more ample and eloquent restatement of Beza’s major themes and more prominent emphasis on the role of the people’s representative structures, but he makes a special effort to portray the lower magistrates as the people’s guardians. These lower magistrates have an obligation to defend their rights.